Effect of acrylic block copolymer on the fracture toughness and glass transition temperature of carbon fabric reinforced 180°C cure-epoxy composites. (12th December 2017) - Choi, Kyung Hoon; Yoo, Dae-Geon; Kim, Gue-Hyun; Ha, Chang-Sik
ABSTRACT: In this study, carbon fabric (CF)/180°C cure-epoxy composite laminates were prepared with an acrylic block copolymer as a toughner. The acrylic block copolymer is known to be self-assembled into nanostructures such as micells and vesicles in epoxy resin. The Mode I interlaminar fracture toughness of CF/180°C-cure epoxy composite laminates was evaluated by the double cantilever beam (DCB) test. The fractured surface and glass transition temperature of the composite were investigated by scanning electron microscopy (SEM) and dynamic mechanical analyzer (DMA), respectively. With increasing content of the acrylic block copolymer from 2.5 to 10 phr, the Mode I interlaminar fracture toughness continuously increases. Addition of the acrylic block copolymer (2.5–10 phr) makes little change in Tg of the CF/180°C-cure epoxy composites.